Life is a rollercoaster…What helps parents cope with the Neonatal Intensive Care Unit (NICU)?. Issue 4 (August 2015) - Stacey, Sarah; Osborn, Mike; Salkovskis, Paul
Abstract The birth of a pre-term baby is an acutely stressful event for parents. Consideration of the factors which help parents cope with NICU can help achieve the best possible outcome for NICU babies. The study objective was therefore to understand better the factors which support coping. A consecutive sample of NICU parents participated in semi-structured interviews which focussed on their experience. The setting was a UK Level 2 NICU and participants were nine parents representing seven families. Thematic analysis was used to analyse the data. The main theme extracted from the data described the Emotional Rollercoaster of NICU. Additional themes identified factors which helped or hindered coping: Baby Wellbeing, Physical Environment and Other People. In conclusion, none of the factors alone explain positive coping, however the findings give useful information about optimal NICU conditions to parental promote psycho-social wellbeing.